It's Me(me), Revolution Elizabeth: Social Media and a Practice of Critical Social Commentary. (October 2022) - Martin, Anne E.; Fournillier, Janice B.
One viral video emerging from the January 6th, 2021 attempted insurrection showed a White woman crying about being maced upon her unlawful entry into the U.S. Capitol. We used intersectional and critical discourse methods to analyze 127 Twitter replies to the video constructing the Revolution Elizabeth meme. Twitter users alluded to popular culture to garner shared understanding and used sarcasm to interrogate White women's privileges, often in contrast to the treatment of Black people. Absent from replies were nuanced considerations of racialized sexism. We argue that the discursive use of humor undercut the agentive possibilities associated with the meme.